Kurikulum Merdeka: Paradigma Baru Inovasi Pembelajaran Abad 21 di Sekolah Dasar - Oktori, Agus Riyan; Yulizah, Yosi; Amrillah, H. M. Taufik; Arif, Mahmud (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The curriculum is a fundamental part of education that must be evaluated innovatively and continuously in accordance with the times and science and technology. The Merdeka Curriculum emerged as an innovation that supports learning that is more flexible and enjoyable for students, and emphasises the development of creativity and freedom of thought. This study aims to understand elementary school teachers' perspectives on the Merdeka Curriculum in the context of 21st century learning innovation. This research uses a qualitative approach by conducting in-depth interviews and focus group discussions (FGDs) with teachers in various primary schools. The data were analysed using thematic analysis to identify patterns and meanings that emerged from teachers' experiences and views on the implementation of the Merdeka Curriculum. The results showed that Merdeka Curriculum supports the development of learners' competencies through project-based learning that hones the soft skills and character of Pancasila learners. Teachers feel flexibility in teaching methods, which allows them to adjust to the abilities and needs of learners and local content. The implementation of Merdeka Curriculum in Indonesia is expected to support educational reforms that are adaptive to changing times, provide opportunities for schools to innovate according to local needs and culture, and create a pleasant learning atmosphere. This research emphasises the importance of the teacher's contribution in implementing the Merdeka Curriculum as a response to today's educational challenges.